1996
DOI: 10.1017/s0954579400007148
|View full text |Cite
|
Sign up to set email alerts
|

Children's treatment by peers: Victims of relational and overt aggression

Abstract: Past research on peer victimization has focused on maltreatment through overtly aggressive behaviors. Although a relational form of aggression has been identified in recent research, studies of the victims of relational aggression have not yet been conducted. The present research was designed as a first attempt to address this issue. Four goals were pursued (n = 474; third- through sixth-grade children): (a) development of a self-report measure of victimization through relational and overt aggression; (b) asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
728
5
16

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 798 publications
(794 citation statements)
references
References 23 publications
38
728
5
16
Order By: Relevance
“…Although some studies suggest that relational/social victimization is more common among girls than boys (e.g., Crick & Bigbee, 1998;Schafer, Werner, & Crick, 2002), many studies indicate no sex difference (e.g., Baldry & Winkel, 2003;Crick & Grotpeter, 1996;Prinstein, Boergers, & Vernberg, 2001 Another set of studies examines stress specifically in the context of dyadic friendships. Studies of middle childhood and adolescent youth generally are consistent in indicating that girls and boys report similar levels of conflict in their friendships (Bukowski et al, 1994;Furman & Buhrmester, 1985;Lempers & Clark-Lempers, 1993;Parker & Asher, 1993;Rose & Asher, 1999 although at least one study favored boys (Patterson et al, 1990) and one favored girls (Forteza, Snyder, Palos, & Tapia, 1996).…”
Section: Sex Differences In Stress and Coping Processesmentioning
confidence: 99%
“…Although some studies suggest that relational/social victimization is more common among girls than boys (e.g., Crick & Bigbee, 1998;Schafer, Werner, & Crick, 2002), many studies indicate no sex difference (e.g., Baldry & Winkel, 2003;Crick & Grotpeter, 1996;Prinstein, Boergers, & Vernberg, 2001 Another set of studies examines stress specifically in the context of dyadic friendships. Studies of middle childhood and adolescent youth generally are consistent in indicating that girls and boys report similar levels of conflict in their friendships (Bukowski et al, 1994;Furman & Buhrmester, 1985;Lempers & Clark-Lempers, 1993;Parker & Asher, 1993;Rose & Asher, 1999 although at least one study favored boys (Patterson et al, 1990) and one favored girls (Forteza, Snyder, Palos, & Tapia, 1996).…”
Section: Sex Differences In Stress and Coping Processesmentioning
confidence: 99%
“…It is well-documented that even these young children experience loneliness and exclusion (e.g., Crick et al, 1996) and prior experimental work has shown that they are sensitive to ostracism primes (Over & Carpenter, 2009;Watson-Jones et al, 2014). Using this age range also enabled a preliminary investigation into when children's understanding of, and responses to, ostracism emerge developmentally.…”
Section: Ostracism)and)affiliation)) ) ) 5)mentioning
confidence: 99%
“…Children's self-reports of victimization of overt and relational bullying at age 11 years were obtained with the Social Experience Questionnaire (SEQ; Crick & Grotpeter, 1996). The SEQ consists of the scales Relational Victimization (e.g., How often does another kid say they won't like you unless you do what they want you to do?)…”
Section: Correlates and Consequencesmentioning
confidence: 99%